Poor glycemic control and abrupt onset of diabetes in HCV patients receiving direct-acting antiviral drugs: case series. (13th July 2018) - Wahid, Braira; Wasim, Muhammad; Saleem, Komal; Waqar, Muhammad; , Sajjad; Wahid, Khansa; Hussain, Manzoor; Idrees, Muhammad
Aim: Hepatitis C virus (HCV) impairs glucose metabolism and interferes with insulin-signaling pathways. About a third of HCV-infected patients develop Type 2 diabetes mellitus. Several evidences correlated direct-acting antiviral (DAA) based treatment of HCV infection with improved glycemic control.Patients & methods: Disturbance in glucose metabolism of two different HCV patients receiving DAA drugs was noticed.Results: We observed the first evidence of abrupt onset of diabetes and poor glycemic control in two different obese patients respectively, following successful treatment of HCV with sofosbuvir and ribavirin.Conclusion: This case is an evidence of potential glucose intolerance in HCV patients receiving DAA drugs. It further suggests the need for regular screening of patient during DAA therapy for early detection of diabetes or poor glycemic control.